Pengabdian kepada Masyarakat: Penyuluhan tentang “Citizen Journalism” sebagai Ekspresi Sikap Demokrasi Kaum Muda - Fensi, Fabianus (Jurnal Pengabdian dan Kewirausahaan, 2023)
The rapid development of communication technology allows the communication community to get and do two things at once. On the one hand, the communication community can easily get the information they need, on the other hand the communication community is now productively creating various information content needed by the community. This seminar is intended to make young people aware,  that there is an opportunity for them to democratically convey news to others in the concept of citizen journalism. This seminar was attended by 89 participants from SMA Budi Mulia. The theme of the seminar was citizen journalism as an expression of the democratic attitude of  people. Citizen journalism is a form of community-based journalistic activity, because it has basic characteristics, such as: participatory, community-based, fact-based information, being an alternative media, socially oriented non-profit, and driven by internet-based social media. On the one hand, the characters can provide various alternative sources of information for the audience, but on the other hand, these characters provide a wide space for public duping, hoaxes, and hate speech. In order to balance the very strong character of information based on freedom, it is necessary to apply various ethical principles in collecting and sharing news in citizen journalism. The ethical principles include: accurate, balanced, fair, complete, objective and clear. By upholding ethical principles, citizen journalism is not only considered an alternative media for information, but also the main media in the process of educating the public. The media educates the public in order to uphold its dignity as a reliable source of information.